Study on serum TL1A levels and their correlation with Th17 cells, IL-17 and IL-21 in children with Graves’ disease - Hao, Lijun; Yang, Jiong; Lian, Biyao; Yin, Chunyan; Xiao, Yanfeng; Liu, Yuesheng (Frontiers in Immunology, 2024)
ObjectiveTo investigate serum TL1A levels and their correlation with Th17 cells, IL-17, and IL-21 in children with Graves’ disease (GD).MethodsThirty-seven children (12 males and 25 females) aged 9-14 years with newly diagnosed and untreated GD were enrolled in this study. Serum TL1A, IL-17, and IL-21 levels were measured using enzyme-linked immunosorbent assay (ELISA). The percentage of Th17 cells in peripheral blood was determined by flow cytometry. The correlation between serum TL1A levels and Th17 cells, IL-17, and IL-21 was analyzed using Pearson’s correlation coefficient.ResultsSerum TL1A levels and the percentage of Th17 cells were significantly higher in children with GD compared to healthy controls (P<0.05). Serum IL-17 and IL-21 levels were also significantly elevated in GD patients (P<0.05). Serum TL1A levels positively correlated with the percentage of Th17 cells (r=0.625, P<0.05), IL-17 (r=0.573, P<0.05), and IL-21 (r=0.542, P<0.05) in children with GD.ConclusionSerum TL1A levels are increased in children with GD and positively correlate with Th17 cells, IL-17, and IL-21, suggesting that TL1A may play a role in the pathogenesis of GD by regulating Th17 cell differentiation and the production of IL-17 and IL-21.